Evolution in the Internal Justice Regime of the United Nations - مهدی حدادی; Seyedmohsen Hekmatimoghaddam (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2017)
Managers and Decision-Makers of All Organizations should understand that they will be Responsible for their decisions. Internal Tribunals of the United Nations are statutory institutions created by the UN General Assembly in response to the need for an independent, transparent, effective, efficient judicial system that would ensure managerial accountability. By these Tribunals, the employees are sure that they can object to unfair and wrong decisions, and demand their rights that are foreseen for them under the rules and statute of the organization. The internal justice regime of the United Nations has changed a lot up to now. The first Administrative Tribunal of the UN was created in 1949, and it looked after the disputes between employees and the organization until the beginning of 21st century. Naturally in these long years its weaknesses were found and tries were made to fix them. Eventually in 2007, the foundation of the new internal justice regime of the UN that was composed of two Tribunals named United Nations dispute Tribunal and United Nations Appeals Tribunal was made. Analysis of Weaknesses and strength of the first and the old internal justice regime, and their comparison is this paper's goal.